Analysis of Indonesia’s Foreign Policy in the Naturalization Process: Legal and Social Implications for National Identity - Sitti Nurtina; Destian Khaldiansyah Rauf; Moh. Falmes Lakadjo; RR. Ananda Mahadewi; Agung Suhabi Putra (Journal of Governance and Global Studies, 2025)
The naturalization of football players seems to be increasingly intensively carried out at this time. The naturalization program for football players in Indonesia began to be discussed in 2010. At that time, Indonesia naturalized footballers such as Cristian Gonzales and Irfan Gonzales. becoming an athlete's nationality is no longer a new thing in the international world. But in the field of sports, the case of naturalization of football players in Indonesia has received less attention from academics. The introduction of foreign talent is supported by national policy, with the aim of strengthening the Indonesian national team towards the World Cup. This paper examines several legal concepts and various phenomena, such as foreign policy, social identity, naturalization, naturalization procedures and legal basis in the life of naturalized football players. The aim is to make the exchange of citizenship of soccer players a case that needs to be discussed in the current state of sports status in Indonesia, in the interaction of sports and society.